Geração de biogás utilizando cama de aviário e manipueira - Suzuki, Ana Beatryz Prenzier (2012)
The demand for energy have been shown to be increasing and to meet this demand is necessary to seek alternative sources of energy. This study aimed to verify the biogas production by mixing the poultry litter with cassava wastewater for obtaining and analyzing their biogas effluent and checking the reduction of organic load. Thus trying to solve the environmental issue of the disposal thereof and producing clean, renewable energy contributing to the Brazilian energy matrix. There were used batch digesters made of vinyl and fed with different mixtures of biomass and thus verified the amount of biogas generated and the biogas quality obtained. We found significant biogas productions of up to 0.39 and 0.30 L d-1 and load reductions which reached 81.94%